1998
DOI: 10.1017/s0079497x00002279
|View full text |Cite
|
Sign up to set email alerts
|

A Late Iron Age Burial from Chilham Castle, near Canterbury, Kent

Abstract: During the spring of 1993 Mr Darren Nichols was searching land near Canterbury with his new metal detector when he made a most interesting discovery. At a shallow depth he unearthed a burial, containing a decorated bronze mirror, a bronze brooch, and the remains of a pot holding cremated bone. The mirror was subsequently identified as being of Iron Age date, bearing a characteristic engraved Celtic design on its reverse. Realising the importance of the find, Mr Nichols reported the discovery to local archaeolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The first, burial 13 at King Harry Lane, St. Albans was assessed as male (Stirland in Stead and Rigby 1989) although no information is given as to how this conclusion was reached. The second, discovered at Chilham Castle, Kent in 1993 was identified as female on the basis of the small size of a mandibular condyle (Parfitt 1998), a tentative indicator at best. Of the seven inhumations analysed since 1960, one, from Bryher on the Isles of Scilly, furnished with a sword and shield as well as a mirror, proved too poorly preserved for either osteological assessment or aDNA analysis (S. Mays pers.comm).…”
Section: Mirrors Burials and Gendered Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first, burial 13 at King Harry Lane, St. Albans was assessed as male (Stirland in Stead and Rigby 1989) although no information is given as to how this conclusion was reached. The second, discovered at Chilham Castle, Kent in 1993 was identified as female on the basis of the small size of a mandibular condyle (Parfitt 1998), a tentative indicator at best. Of the seven inhumations analysed since 1960, one, from Bryher on the Isles of Scilly, furnished with a sword and shield as well as a mirror, proved too poorly preserved for either osteological assessment or aDNA analysis (S. Mays pers.comm).…”
Section: Mirrors Burials and Gendered Assumptionsmentioning
confidence: 99%
“…Consideration has recently been made concerning the placement of well-furnished Iron Age burials with mirrors in the landscape, some being established towards the top of an escarpment, overlooking river systems as single, comparatively isolated deposits placed in a prominent locale (Joy 2011, 473). The burial with a mirror from Latchmere Green, in Hampshire, for example looked down on a number of rivers, including a tributary of the Thames (Fulford and Creighton 1998), whilst examples from Chilham Castle, Kent (Parfitt 1998), Birdlip, Gloucestershire (Staelens 1982) and Dorton, Buckinghamshire (Farley 1983), had extensive views of the Great Stour, Severn valley and Vale of Aylesbury respectively. Joy has suggested that Iron Age burials with mirrors tend to be clustered, identifying four chronologically and geographically distinct concentrations in the UK: East Yorkshire; Cornwall and the Isles of Scilly; western; south-east and southern England (Joy 2011, 470-471).…”
Section: Landscape Settingmentioning
confidence: 99%